Pelatihan Kewirausahaan Berbasis Digital Bagi Peserta Perkemahan di Kabupaten Labuhanbatu - Purnama, Iwan; Al Maahi, Muhammad Zuhri; Hasibuan, Linda Suhela (Jurnal Pengabdian Masyarakat Gemilang (JPMG), 2022)
The aim of this entrepreneurship training is to provide an understanding of digital marketing for Scouts of Labuhanbatu Regency so that they have competence in the field of digital-based entrepreneurship and have an entrepreneurial spirit when they graduate from school. This training was created by utilizing social media (Facebook, Instagram) and Marketplace (Shopee, Tokopedia, Bukalapak) as current digital marketing media. Social Media and Marketplaces are one of the media that is currently developing and can help in carrying out digital marketing (Digital Marketing). The activity method in implementing it uses various methods such as lectures, discussions, questions and answers, as well as providing digitalization training. The results of the activity provided digital marketing training for Camp Participants in Labuhanbatu Regency to have digital-based entrepreneurial skills.